Faktor-Faktor Yang Mepengaruhi Harga Saham Pada Perusahaan PT Batulicin Nusantara Maritim Di Bursa Efek Indonesia - Rijal, Muhammad (PERFORMA, 2023)
The stock price is one of the benchmarks or a sign of a company’s financial stability, with a stable stock price it will also make a company still trusted by the public. The purpose of this study is to explore the factors that can affect the stock price of PT Batulicin Batulicin Nusantara Maritim listed on the IDX during the 2019-2021 period, especially in financial ratios in the form of Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), Book Vale per Share (BVS), Debt to Equity Ratio (DER). An associative quantitative approach and method kausal is the choice in this study, using SPSS with the Classical Assumption Test, t-test, and f-test. in the Partial T test that was carried out, each of the variables Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS) were effect on stock prices while book value per share (BVS), debt equity ratio (DER) has a negative effect on stock prices. Then in the Simultaneous F test shows all variables Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), Book Value per Share (BVS), Debt to Equity Ratio (DER) together affect the stock price in mining company. The conclusion in this study, it is important for companies to consider many factors in maintaining stock price stability, as an effort to maintain the company’s existence in maintaining public trust as users or consumers amd the benefits of this research are to increase investor awareness of activities and company insight so that they can compete to become a go public company. Keywords: ratio return on asset (ROA), return on equity (ROE), earning per share (EPS), book value per share (BVS), debt equtity ratio (DER), Stock Price